Simulation of the second ETEX release in the proximity of the source. (1st January 2000) - Bellasio, R.; Bianconi, R.; Mosca, S.; Girardi, F.; Graziani, G.; Klug, W.
The complexity of the weather situation during the second release of ETEX (European Tracer EXperiment) resulted in generally poor performances of the long-range dispersion models employed in the real time simulation of the release. On the other hand, much more detailed meteorological information than those available to the real time modellers were assembled in the course of the experiment and stored in a data bank. This has allowed the possibility of investigating with a much finer mesh interval the mesoscale flow over a few hundreds kilometres range from the source, using a model that could take into account the terrain topography. The resulting flow was used as input to a Lagrangian particle and a Lagrangian puff model that simulated the cloud development for the first hours after the release start. The comparison between calculated and measured tracer concentrations was carried on for a number of sites close to the release site. The result indicated that some of the peculiarities in the dispersion found by the experiment were reproduced, thereby enhancing the importance of this type of approach.